Crossbones - Farah, Nuruddin, 1945- (New York : Riverhead Books, 2011)
"A gripping new novel from today's "most important African novelist" . (The New York Times Review of Books) A dozen years after his last vis it, Jeebleh returns to his beloved Mogadiscio to see old friends. He is accompanied by his son-in-law, Malik, a journalist intent on covering the region's ongoing turmoil. What greets them at first is not the chao s Jeebleh remembers, however, but an eerie calm enforced by ubiquitous white-robed figures bearing whips. Meanwhile, Malik's brother, Ahl, has arrived in Puntland, the region notorious as a pirates' base. Ahl is s earching for his stepson, Taxliil, who has vanished from Minneapolis, a pparently recruited by an imam allied to Somalia's rising religious ins urgency. The brothers' efforts draw them closer to Taxliil and deeper i nto the fabric of the country, even as Somalis brace themselves for an Ethiopian invasion. Jeebleh leaves Mogadiscio only a few hours before t he borders are breached and raids descend from land and sea. As the une asy quiet shatters and the city turns into a battle zone, the brothers experience firsthand the derailments of war. Completing the trilogy tha t began with Links and Knots, Crossbones is a fascinating look at indiv iduals caught in the maw of zealotry, profiteering, and political confl ict, by one of our most highly acclaimed international writers. "--
"Completing the trilogy that began with LINKS and KNOTS, Jeebleh ret urns to Somalia, now in a religionist grip, along with his journalist s on-in-law, Malik, and Malik's brother Ahl, who is in search of his step son-turned-pirate"--
Includes bibliographical references (p. [387]-389).
Keywords: Americans -- Somalia -- Fiction; Mogadishu (Somalia) -- Fiction; Political fiction